2008
DOI: 10.1007/s11916-008-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Classification of pediatric headache

Abstract: The high incidence and prevalence of headaches in the pediatric population has a significant impact on patients and their families. Migraine, the most common headache disorder for which pediatric patients see a physician, remains underdiagnosed. Recent studies have revealed the increasing incidence of migraine and chronic migraine in the pediatric population. This article presents limitations of the present diagnostic criteria for migraine, and the proposed modifications to these criteria may assist the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…25,26 One study of adolescents reported that only 16% were prescribed medications to treat their migraines. 26 A study in adults with epilepsy and migraine reported that 4% of patients with both conditions were treated with a prescription medication for the headaches even though 33% had been diagnosed with severe headaches. 5 Several possible explanations exist for these findings in our cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 One study of adolescents reported that only 16% were prescribed medications to treat their migraines. 26 A study in adults with epilepsy and migraine reported that 4% of patients with both conditions were treated with a prescription medication for the headaches even though 33% had been diagnosed with severe headaches. 5 Several possible explanations exist for these findings in our cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Our population was compared to historical controls in order to compare our series to the overall prevalence of migraine alone, which does not allow for a direct cohort comparison. 25,26 Although it would have been ideal to have a group of patients with migraine alone to compare other demographics to, the primary purpose was to evaluate risk factors of seizure disorders. Parents generally filled out the questionnaires so it is possible that they did not know the extent of their children's headaches and the children's answers to the questions may have varied from their parents' if asked themselves or alone.…”
Section: Resultsmentioning
confidence: 99%
“…However, a significant course effect was reported. A tendency was found that at the end of the training and 6 months later the Biofeedback training condition without relaxation and parental inclusion showed better results [4, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pediatric headaches has increased significantly during the last 30 years in western countries as well as in Asia [14]. To compound matters, these headache conditions often have significant negative social and economic impacts [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…Occipital pain is frequently found in brain tumors. 4,13 In several studies children with serious underlying conditions had demonstrable objective finding on neurological examination. The importance of a good history and thorough physical examination cannot be overemphasized.…”
Section: Secondary Headachesmentioning
confidence: 99%